Cyfrowy kult przodków – aplikacja Deep Nostalgia jako nowa forma mediatyzacji pamięci religijnej - Iwanicki, Juliusz (Humaniora. Czasopismo Internetowe, 2021)
The paper analyzes a particular example of the expansion of popular culture through a specific mediatization of old photographs and paintings, which consists in transforming works of art into short, simulated videos. This new technology was interpreted using religious categories with references to ancestor worship and cultural studies with the paradigm of memory studies. It was theorized that the new processes of mediatization are changing the religious memory of society.